A Model For Developing Students' Technical Literacy In Technology Lessons Based On Elements Of Robotics - Jabborova Umida Yusupovna (European International Journal of Pedagogics, 2025)
The rapid technological transformation of society demands that learners acquire technical literacy not as isolated knowledge but as integrated competence. This study proposes a Cognitive Apprenticeship (CA) model tailored for technology lessons that leverages elements of educational robotics to develop students’ technical literacy. The model situates learning in authentic, problem-centered robotic tasks, making tacit expert strategies visible through modeling, coaching, and scaffolding, and gradually fading support toward independent application. The implementation framework articulates how robotics activities are structured to foster understanding of technical systems, procedural fluency, critical evaluation, and adaptive problem solving. Evidence from contemporary research demonstrates that embedding robotics within a CA approach enhances engagement, higher-order thinking, and transfer of technical skills. The proposed model is adaptable to diverse school contexts and provides a coherent pathway from guided participation to autonomous technical agency. Keywords: cognitive apprenticeship model, technical literacy, educational robotics, technology education, STEM integration, instructional design, authentic learning.